Restorative Justice Approach towards Termination Investigation of Begal Victims Based on Noodweer Action and Noodweer Exes - Herman Katimin; Ida Farida (Jurnal Wawasan Yuridika, 2022)
In cases of involuntary manslaughters in self-defense by a victim of violent armed robberies (begal), investigators have often been reluctant to implement Article 49 of the Indonesian Criminal Code as a legal ground to terminate criminal investigations. The study aimed to analyze the termination of investigations based on noodweer and noodweerexces through a restorative justice approach. The study was descriptive and qualitative, employing a descriptive method. Data were collected from relevant literature and were analyzed quantitatively. The results showed that in the cases of involuntary manslaughter in self-defense by victims of violent armed robbery, the investigators had the authority to terminate the investigation and implement a restorative justice approach instead. It was applicable when the victims’ self-defense was void of mens rea, compelled by force, or done in defense of his or another person’s physical or sexual integrity or property against an immediate, unlawful attack. The restorative justice approach may involve the victims and/or their families, the perpetrators’ families, religious leaders, community leaders, traditional leaders, youth leaders, and other relevant stakeholders and is aimed solely for the sake of justice, legal usefulness, and legal certainty.